2020
DOI: 10.1002/ps.5929
|View full text |Cite
|
Sign up to set email alerts
|

Metribuzin resistance via enhanced metabolism in a multiple herbicide resistant Lolium rigidum population

Abstract: BACKGROUND: The photosystem II (PSII)-inhibiting herbicides are important for Australian farmers to control Lolium rigidum Gaud. and other weed species in trazine tolerant (TT)-canola fields. A L. rigidum population (R) collected from a TT-canola field from Western Australia showed multiple resistance to PSII, acetyl-coenzyme A carboxylase (ACCase) and acetolactate synthase (ALS) inhibitors. The mechanisms of multiple resistance in this R population were determined. RESULTS: The R population showed a low-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…A similar HPLC protocol was used for metribuzin metabolism studies in the metribuzin-resistant crop lupin 27) and weed species of Raphanus raphanistrum 27) and L. rigidum. 42) Although it is not possible to draw a clear conclusion due to the lack of peak identifications, the results in this paper showed an increase in polar metabolites (Fig. 3), similar to the HPLC profile in the resistant species studied (e.g., major polar metabolites eluted during 10-15 min).…”
Section: Discussionsupporting
confidence: 66%
“…A similar HPLC protocol was used for metribuzin metabolism studies in the metribuzin-resistant crop lupin 27) and weed species of Raphanus raphanistrum 27) and L. rigidum. 42) Although it is not possible to draw a clear conclusion due to the lack of peak identifications, the results in this paper showed an increase in polar metabolites (Fig. 3), similar to the HPLC profile in the resistant species studied (e.g., major polar metabolites eluted during 10-15 min).…”
Section: Discussionsupporting
confidence: 66%
“…However, the total FPB metabolism difference between Sus and R barnyardgrass observed in the present study was too small to infer the FPB resistance mechanism. In addition, other previous studies for resistance mechanisms of 2,4‐D, imazamox, glufosinate, and metribuzin have revealed that enhanced metabolism is commonly found in resistant weeds 25–28 . Thus, to elucidate the relationship between FPB resistance and metabolism, it was necessary to investigate what types of metabolites were produced in Sus and R barnyardgrass at each sampling time and how they were involved in the FPB sensitivity/resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Evans et al (2017) found that a single GST enzyme, AtuGSTF2, correlated strongly with PS II resistance in A. tuberculatus. In other weed species, NTSR has been found to confer PS II-inhibitor resistance by P450 monooxygenase, which was recently reported to confer metribuzin resistance in rigid ryegrass (Lolium rigidum Gaudin) in Australia (Ma et al 2020). Amaranthus tuberculatus with PS II resistance due to NTSR is resistant to atrazine but sensitive to metribuzin (Patzoldt et al 2003;Vennapusa et al 2018).…”
Section: Introductionmentioning
confidence: 99%